Proteoglycans as Therapeutic Targets in Brain Cancer - Yan, Zoya; Wang, Shanzhi (Frontiers in Oncology, 2020)
Proteoglycans are diverse, complex extracellular surface macromolecules composed of a central core protein with covalently linked glycosaminoglycan (GAG) chains, both of which contribute to the growing list of crucial bio-active functions attributed to proteoglycans. Extracellular proteoglycans, including heparan sulfate and chondroitin sulfate, play critical roles in the regulation of cell signaling and migration via interactions with extracellular ligands, growth factor receptors, extracellular matrix components, intracellular enzymes, and structural proteins. In cancer, proteoglycans drive multiple oncogenic pathways in tumor cells and promote critical tumor-microenvironment interactions. Recently, research has focused on the role of proteoglycans in nervous tissue development due to their highly regulated expression patterns, which promote or inhibit neurite outgrowth, participate in specification and maturation of various precursor cell types, and regulate cell behaviors like migration, axonal pathfinding, synaptogenesis, and plasticity. The present review summarizes current progress for the studies of proteoglycan function in brain cancer and discusses the latest insights into the roles of brain glycoproteins as modulators of cell adhesion, migration, neurite outgrowth, and glial tumor invasion. Furthermore, we demonstrate an association between specific proteoglycan alterations and the suggested cancer-associated proteoglycans as novel biomarkers for therapeutic targets.